5(y-6)-16=-11

Simple and best practice solution for 5(y-6)-16=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(y-6)-16=-11 equation:


Simplifying
5(y + -6) + -16 = -11

Reorder the terms:
5(-6 + y) + -16 = -11
(-6 * 5 + y * 5) + -16 = -11
(-30 + 5y) + -16 = -11

Reorder the terms:
-30 + -16 + 5y = -11

Combine like terms: -30 + -16 = -46
-46 + 5y = -11

Solving
-46 + 5y = -11

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '46' to each side of the equation.
-46 + 46 + 5y = -11 + 46

Combine like terms: -46 + 46 = 0
0 + 5y = -11 + 46
5y = -11 + 46

Combine like terms: -11 + 46 = 35
5y = 35

Divide each side by '5'.
y = 7

Simplifying
y = 7

See similar equations:

| 35*7=(X*7)+(5*7) | | 3=12+k | | 8(8)(-7)(-6)= | | 2a+ab=18 | | x=4x^2-25 | | 22.5x-15=120 | | 6-15-(-9)= | | b-10=15 | | 9x^1+7x^2=63 | | 0.5m+15=0.25m+25 | | 3x=8-8 | | 3.5-5=x | | 6b+14=3b-21 | | X=2y+4y+1 | | 0.5m+15=0.25+25 | | x+16=7+4x | | -6+(-7)+16+(-5)= | | -6(6x-6)+(4x-8)= | | 5(x+2)=3(x+3) | | -2(2t+3)=-14 | | 2y+6x=-10 | | 0=20x^2+27x-8 | | 10+5r-14+2r-3r= | | 3(f-7)=-6 | | 4=x^3-5 | | 198=x^2+3x | | 1.25+3.5=-2.75 | | 9+h=4 | | r+15=9+4r+6 | | 45n=22.5 | | 5x+4x=4+8 | | 6x-8=8x-22 |

Equations solver categories